KINDS OF PACKAGE, INITIAL MOISTURE CONTENTS AND STORAGE PERIODS OF BEAN SEEDS - ALVES, Antonio Carlos; LIN, Hiow Shong (Scientia Agraria, 2003)
The objetive of this work was to evaluate the physiological quality of bean seeds under different kinds of package, initial seed moisture contents and natural storage condition for 21 months. Bean seeds (cv. Carioca) with 11% and 15% of moisture contents were packed in three kinds of package (cloth bags of cotton, bags of polyethylene and thick plastic), then, were stored in seed laboratory of plant Science Department, Agricultural Science Center, Federal University of Santa Catarina. Seed moisture content, germination and vigor were determined in each three months until 21 months. Independently to the kinds of package and initial seed moisture contents, seeds with lower moisture contents, had higher germination and vigor. The higher seed germination and vigor were found when the initial seed moisture content was in 11%. Seeds packed in polyethylene bags had higher seed vigor, however, the seed germinations were not affected by the different kinds of package. Seeds with 11% moisture contents and packed in polyethylene bag had the highest seed vigor. The seed vigor and germination decreased rapidly after six and 12 months of storage, respectively.